A Semiotic Network Comparison of Technocratic and Populist Discourses in Turkey - Sueerdem, Ahmet K. (Springer, 2009)
This chapter argues that despite the convergence of their superficial contents, political and technical discourses are still substantially different in terms of the semiotic structures embodying their logic of articulation. The semiotic structures of populist and technocratic discourses are empirically elicited and compared through a semiotic mapping methodology based on the principles of mathematical network analysis and interpretive semiotic analysis. Findings suggest evidence about the differentiation Of Populist and technocratic discourses in terms of their semiotic structures for the samples collected from the Turkish political context. Despite its limitations, the semiotic mapping approach developed in this study offers promising methods for bridging the quantitative and qualitative methods for the analysis of policy discourses.
Annual Conference of the Societe-Quebecoise-de-Science-Politique -- MAY 24-25, 2007 -- Quebec City, CANADA
Keywords: Latin-America; Neoliberalism